2021
DOI: 10.1016/j.celrep.2021.109197
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 genomic surveillance identifies naturally occurring truncation of ORF7a that limits immune suppression

Abstract: SARS-CoV-2 genomic surveillance identifies naturally occurring truncation of ORF7a that limits immune suppression Graphical abstract Highlights d ORF7a mutations are found in SARS-CoV-2 genomes isolated from around the globe d The ORF7aD115 isolate displays a replication defect d An ORF7a mutation limits viral suppression of the interferon response

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
89
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(96 citation statements)
references
References 76 publications
2
89
0
Order By: Relevance
“…Interestingly, several independent studies have reported SARS-CoV-2 isolates with unique in-and out-of-frame deletions in Orf7a resulting in heavily truncated and/or non functional polypeptides 28,29 . Although the implications of these mutations are not completely understood at present, we observe that more recently, depletion of Orf7a has been linked with reduced inactivation of the host immune system by SARS-CoV-2 30 . Globally, the 26 aforementioned lineages associated with multiple HGs include about 67%…”
Section: Functional Evaluation Of High Frequency Variants Fixed In Distinct Hgsmentioning
confidence: 75%
See 1 more Smart Citation
“…Interestingly, several independent studies have reported SARS-CoV-2 isolates with unique in-and out-of-frame deletions in Orf7a resulting in heavily truncated and/or non functional polypeptides 28,29 . Although the implications of these mutations are not completely understood at present, we observe that more recently, depletion of Orf7a has been linked with reduced inactivation of the host immune system by SARS-CoV-2 30 . Globally, the 26 aforementioned lineages associated with multiple HGs include about 67%…”
Section: Functional Evaluation Of High Frequency Variants Fixed In Distinct Hgsmentioning
confidence: 75%
“…Our finding that approximately 9% of all current SARS-CoV-2 isolates in the B.1.1.7 lineage carry a truncated form of the orf7A protein is also particularly relevant. Indeed, orf7a was recently shown to inhibit IFN-I signaling 30 while genetic defects in IFN-I signaling in the host have been recently linked with more severe forms of COVID-19 36 . Taken all together these observations might suggest again the potential emergence of less pathogenic/attenuated strains in B.1.1.7.…”
Section: Discussionmentioning
confidence: 99%
“…In the SARS-CoV-2 genome, mutations distribute over genes coding basic structural proteins of the virus and ORFs (open reading frames) [ 36 , 37 , 38 ]. ORFs are defined as contiguous stretches with a start and a stop codon and a ‘protein-coding’ meaning, i.e., translation into a functional protein that contributes to viral transmission, replication, immune avoidance or overall fitness or that can encode an antigen detectable by the immune system or a diagnostic test [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…ORF7A is a type 1 transmembrane protein and it has numerous putative functions involved in host-pathogen interactions and immune evasion (Nemudryi et al, 2021). ORF7A truncations in SARS-CoV-2 isolates have been discovered before, possibly associated with reduced capacity to subvert the innate immune response (Nemudryi et al, 2021). However, the previous work was carried out using non-clinically relevant cell models, such as Vero or HEK-derived lines.…”
Section: Phenotypic Differences Between Sars-cov-2 'Phe' and 'Bt201' P4mentioning
confidence: 99%
“…The mutations T4685I arose with P812R possibly suggesting genetic linkage, although this remains to be determined.It is of interest that BT20.1 carries a deletion in ORF7A that results in a frameshift and C-terminal truncation of the protein, likely ablating the transmembrane domain and tail. ORF7A is a type 1 transmembrane protein and it has numerous putative functions involved in host-pathogen interactions and immune evasion(Nemudryi et al, 2021). ORF7A truncations in SARS-CoV-2 isolates have been discovered before, possibly associated with reduced capacity to subvert the innate immune response(Nemudryi et al, 2021).…”
mentioning
confidence: 99%